The islamic law of nations: Shaybani's Siyar - Shaybānī, Muḥammad ibn al-Ḥasan approximately 750-804 or 805 (The Johns Hopkins Press, 1966)
A foundational text of the leading school of law in Sunni Islam, it provides essential insights into relations between Islamic nations and the larger world from their earliest days up to the present